2017
DOI: 10.1115/1.4035397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Softening on Anisotropy and Ductile Mode Cutting of Sapphire Using Micro-Laser Assisted Machining

Abstract: Ceramics and semiconductors have many applications in optics, micro-electro-mechanical systems, and electronic industries due to their desirable properties. In most of these applications, these materials should have a smooth surface without any surface and subsurface damages. Avoiding these damages yet achieving high material removal rate in the machining of them is very challenging as they are extremely hard and brittle. Materials such as single crystal silicon and sapphire have a crystal orientation or aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In laser beamassisted cutting of silicon, the surface roughness was improved and the radial spokes which are caused by the crystallographic orientation effect can be eliminated [209]. The anisotropy effect of the single-crystal C-plane sapphire on the ductile mode cutting was investigated in laser-assisted cutting technology [210]. The results showed that for different cutting directions, the critical UCT was improved by applying this technology.…”
Section: Influence Of Brittle Materialsmentioning
confidence: 93%
See 2 more Smart Citations
“…In laser beamassisted cutting of silicon, the surface roughness was improved and the radial spokes which are caused by the crystallographic orientation effect can be eliminated [209]. The anisotropy effect of the single-crystal C-plane sapphire on the ductile mode cutting was investigated in laser-assisted cutting technology [210]. The results showed that for different cutting directions, the critical UCT was improved by applying this technology.…”
Section: Influence Of Brittle Materialsmentioning
confidence: 93%
“…It is widely used in processing of materials [218], such as cutting, welding, marking and sintering. Besides that, it is also used in assisting the cutting of brittle materials, such as the silicon [209] and sapphire [210]. In laser beamassisted cutting of silicon, the surface roughness was improved and the radial spokes which are caused by the crystallographic orientation effect can be eliminated [209].…”
Section: Influence Of Brittle Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, at high temperatures, plasticity plays a greater role in the fracture and deformation processes primarily as a result of thermally generated defects and thermal softening processes (Ref 83,84). Accordingly, to further augment the ductile response of hard-brittle materials, the machining process can be coupled with a heat source, e.g., laser (Ref [85][86][87][88][89]. Recently, SPDT has been coupled with the l-LAM technique to preferentially heat and soften the high-pressure metallic phase during scratching/cutting.…”
Section: (Ref 65)mentioning
confidence: 99%
“…In fact, the preferable absorption wavelength of sapphire is about 200 nm [ 11 , 12 , 13 ]. There are several methods of processing SCS, such as ultrasonic assisted grinding process [ 14 ], UV laser cutting, micro-laser assisted machining [ 15 , 16 ], and LIPAA.…”
Section: Introductionmentioning
confidence: 99%